Long-term changes in mandibular and facial widths after mandibular setback surgery using intraoral vertical ramus osteotomy. Issue 9 (September 2016) - Choi, Y.J.; Ha, Y.-D.; Lim, H.; Huh, J.-K.; Chung, C.J.; Kim, K.-H.
Abstract: This study was performed to evaluate the long-term changes in mandibular width, lower facial width, and ramus angulation after intraoral vertical ramus osteotomy (IVRO) and to identify the factors influencing these changes. This retrospective study included 53 consecutive patients with mandibular prognathism who underwent IVRO with ( n = 33) or without ( n = 20) Le Fort I osteotomy. Postero-anterior cephalograms and frontal facial photographs obtained before, 1 month after, and at least 24 months after IVRO were used for measurements. A linear mixed model and paired t -tests were used to analyze temporal changes and the associated influencing factors. The mandibular width increased immediately after surgery ( P < 0.05), but decreased continuously thereafter. The ramus angulation showed negligible change within the first month ( P > 0.05) and decreased thereafter up to approximately 36 months. The amounts of mandibular setback and posterior impaction and the length of time postoperative influenced these changes. The lower facial width changed, although inconsistently, within 3 mm over time ( P > 0.05). In conclusion, the mandibular width increased after IVRO but seemed to normalize within approximately 3 years. The lower facial width did not reflect underlying skeletal changes. Therefore, long-term transverse changes after IVRO can be considered clinically irrelevant.